Pengaruh Partisipasi Anggaran Terhadap Kinerja Aparat Pemerintah Daerah Provinsi Nusa Tenggara Timur dengan Pemoderasi Transparansi Anggaran - Adoe, Maryanti H. (Journal of Economics Review (JOER), 2025)
Purpose: This study aims to analyze the direct effect of budget participation on the performance of local government officials and the moderating effect of budget transparency. Research Method: The study was conducted using 138 respondents from a total population of 185 employees of the East Nusa Tenggara Provincial Government. The study was quantitative in nature, using moderated regression analysis with the help of SmartPLS 3.00. Results and Discussion: The results of the study show that: 1) Budget participation has a positive and significant effect on the performance of government officials, and 2) Budget transparency does not strengthen the relationship between budget participation and the performance of government officials. Implications: Future studies need to expand the scope of research variables such as organizational culture, leadership, and other factors.